DIGITAL MORTGAGE BANKING ACCEPTABILITY IN PHILIPPINE UNIVERSAL BANKS: EVIDENCE FROM UTAUT MODEL - Dave T. Morales; Fernando L. Trinidad, Ph.D. (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
The changing consumer behaviour all over the world has resulted in the shift of businesses into becoming client-centric. Clients nowadays want convenience, faster processes, seamless transactions, and instant service. The banking sector is not excused with these changes. In fact, bank clients want the same; bank services at the tip of their fingertips. So how should banks respond to these growing demands of clients? Involving technology in bank operations will ensure faster, more convenient, and more seamless transactions as this allows clients to access bank services anytime and anywhere. This study particularly paid attention to the digitization of mortgage banking using the UTAUT model to better understand its acceptability among its clients. The empirical results found that the determinants of behavioural intention to accept digital mortgage device among mortgage clients were facilitating conditions, performance expectancy and effort expectancy. Furthermore, results revealed that performance expectancy is directly related to internet time, frequency of product purchase using a mobile device and use of mobile banking.